Study the Mechanism of Color Depigmentation by Q-Switched Nd-Yag Laser Photoacoustic Shouckwave - Salman Abass, Alaa Hashim; Saleh, Ahmed Haitham Mahidi; sukban, Sarah latif sadiq; sabaar, Wafa' halawi eadhab; jawad, Rana haitham fadil (American Journal of Botany and Bioengineering, 2024)
his project aims to investigate the efficacy and safety of utilizing Q- switched Nd: YAG laser technology generating photoacoustic shockwave for color depigmentation in dermatological applications. The proposed research seeks to address the increasing demand for advanced treatments for various pigmentation disorders, including hyperpigmentation, melasma, post-inflammatory hyperpigmentation and hair bleaching. The project will involve an exploration of the photoacoustic effect induced by Qswitched Nd: YAG laser pulses on pigmented skin lesions. By leveraging the ability of laser-induced shockwaves to disrupt melanin pigment within the skin and hair, the study aims to achieve selective depigmentation while minimizing damage to surrounding tissues.